FINANCIAL MECHANISM OF CAPITALIZATION OF THE LANDRESOURCES OF AGRICULTURAL ENTERPRISES OF THE REGION IS IN MUTUAL RELATIONS WITH TERRITORIAL COMMUNITIES - Levandivskyi , O.T.; Balaniuk, I.F.; Shelenko, D.I.; Sas, L.S. (The actual problems of regional economy development, 2021)
The financial mechanism of capitalization of the land resources of agricultural enterprises in mutual relations with territorial communities, stages of his forming is considered in the article. Attention is accented on the necessity of market capitalization of earth of the agricultural setting for mutual relations with territorial communities. Examined and methodical approaches are analysed in the money estimation of the landed resources. The normative money estimation of earth of the agricultural setting is represented in Ukraine after agricultural lands. The analysis of rent is conducted in relation to the use of earth of the agricultural setting after regions. It is investigated the main types of assessment of land resources depending on the purpose and methods of its carrying out. The analysis of legal acts regulating the procedure of conducting an assessment of land resources assessment is carried out. It is determined that the value at which land resources are reflected in the accounting depends on the way they are acquired of ownership and / or use, as well as the purpose of their use. It is established that in accounting to estimate of land resources the following types of values are used: initial (historical (actual) cost or fair value) and overestimated. The following main methods were used in the research process: system-structural and abstract (for theoretical generalizations of the results of analytical calculations and formulation of conclusions); analysis and synthesis (to detail the object of study through its division into individual components and summarizing the results of their study into one whole); method of comparative analysis (to justify the use of certain tools to regulate production and management relations); economic-statistical - grouping, correlation-regression analysis (to identify the influence of factors on some of its criteria); calculated and constructive (in the development of development strategy). It is well-proven that with forming of market of earth of question from the normative money estimation of earth of the agricultural setting acquire new maintenance and need further research. Displacing attention on the mutual relations of territorial communities and agricultural enterprises in relation to filling of local budget paying for the use of the landed resources. Capitalization of the land resources is certain with gradual transformation them in a capital for the sake of increase of market price. Considerable differentiation of cost of agricultural earth is educed in the regions of Ukraine by normatively money estimation. Attention is concentrated on the considerable underestimation of the land resources and long term of their capitalization. With the aim of transformation of the land resources in financial assets suggestions are reasonable in relation to the improvement of financial mechanism of capitalization of the landed resources in an agrarian sector. In particular, it is marked on the system of expert and normatively money estimation of earth, forming and development of market infrastructure.